Enhanced Enzyme Activity through Scaffolding on Customizable Self‐Assembling Protein Filaments. Issue 20 (28th March 2019) - Lim, Samuel; Jung, Gi Ahn; Glover, Dominic J.; Clark, Douglas S.
Abstract: Precisely organized enzyme complexes are often found in nature to support complex metabolic reactions in a highly efficient and specific manner. Scaffolding enzymes on artificial materials has thus gained attention as a promising biomimetic strategy to design biocatalytic systems with enhanced productivity. Herein, a versatile scaffolding platform that can immobilize enzymes on customizable nanofibers is reported. An ultrastable self‐assembling filamentous protein, the gamma‐prefoldin (γ‐PFD), is genetically engineered to display an array of peptide tags, which can specifically and stably bind enzymes containing the counterpart domain through simple in vitro mixing. Successful immobilization of proteins along the filamentous template in tunable density is first verified using fluorescent proteins. Then, two different model enzymes, glucose oxidase and horseradish peroxidase, are used to demonstrate that scaffold attachment could enhance the intrinsic catalytic activity of the immobilized enzymes. Considering the previously reported ability of γ‐PFD to bind and stabilize a broad range of proteins, the filament's interaction with the bound enzymes may have created a favorable microenvironment for catalysis. It is envisioned that the strategy described here may provide a generally applicable methodology for the scaffolded assembly of multienzymatic complexes for use in biocatalysis. Abstract : A versatile scaffolding platform that can immobilize enzymes on customizable protein nanofibers is reported. An ultrastable self‐assembling filamentous protein, the gamma‐prefoldin, is engineered to specifically and stably bind enzymes using SpyCatcher–SpyTag chemistry. Two different model enzymes, glucose oxidase and horseradish peroxidase, are used to demonstrate that scaffold attachment can enhance the intrinsic catalytic activity of the immobilized enzymes.